Analisis Kegiatan Bank dalam Penyaluran Kredit Bermasalah Studi Kasus Gagal Bayar Kredit di PT Bank Century Tbk - George Muhammad Maulana Helmy Gozali; Jasmine Az-zahra; Naila Syafa AzZahra (Journal of Economics, Management, and Accounting, 2026)
This study analyzes banking activities in managing non-performing loans through a case study of credit default at PT Bank Century Tbk. The research focuses on examining credit distribution patterns, risk management practices, and legal as well as governance implications arising from problematic loans. The findings indicate that the accumulation of non-performing loans was driven by aggressive credit expansion, inadequate creditworthiness analysis, and weak post-disbursement supervision. Credit restructuring and collection efforts were implemented; however, these measures were largely ineffective due to the deteriorating financial condition of debtors. The failure to control credit risk not only affected the bank’s financial performance but also triggered legal disputes, governance issues, and a decline in public trust. The case of Bank Century highlights the importance of prudent lending policies, integrated risk management, and strong corporate governance in maintaining banking stability. This study contributes to the literature by providing an in-depth understanding of how weaknesses in credit management and oversight can lead to systemic banking problems and emphasizes the need for preventive rather than reactive approaches in handling non-performing loans.